2003
DOI: 10.1161/01.hyp.0000072335.73748.0d
|View full text |Cite
|
Sign up to set email alerts
|

Administration Time–Dependent Effects of Aspirin on Blood Pressure in Untreated Hypertensive Patients

Abstract: Abstract-Previous studies on the potential influence of aspirin on blood pressure have not taken into consideration the chronopharmacological effects of nonsteroidal anti-inflammatory drugs. This pilot study investigates the effects of aspirin on blood pressure in untreated hypertensive patients who received aspirin at different times of the day according to their rest-activity cycle. We studied 100 untreated patients with mild hypertension (34 men and 66 women), 42.5Ϯ11.6 (meanϮSD) years of age, randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 46 publications
2
30
0
1
Order By: Relevance
“…10 Most important, the administration time-dependent influence of ASA on BP was demonstrated previously in a randomized trial on healthy women 9 and other independent double-blind, randomized, placebo-controlled clinical trials conducted: first on clinically healthy subjects, 11 a second on normotensive and hypertensive subjects, 12 a third on pregnant women at high risk for preeclampsia, 13 and a fourth in untreated patients with mild hypertension. 14 The findings of these BP studies, all of which used ambulatory BP monitoring (ABPM) to derive primary outcome variables, are consistent; BP-lowering effect of low-dose ASA is achieved when administered at bedtime but not on awakening.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…10 Most important, the administration time-dependent influence of ASA on BP was demonstrated previously in a randomized trial on healthy women 9 and other independent double-blind, randomized, placebo-controlled clinical trials conducted: first on clinically healthy subjects, 11 a second on normotensive and hypertensive subjects, 12 a third on pregnant women at high risk for preeclampsia, 13 and a fourth in untreated patients with mild hypertension. 14 The findings of these BP studies, all of which used ambulatory BP monitoring (ABPM) to derive primary outcome variables, are consistent; BP-lowering effect of low-dose ASA is achieved when administered at bedtime but not on awakening.…”
mentioning
confidence: 78%
“…10 Most important, the administration time-dependent influence of ASA on BP was demonstrated previously in a randomized trial on healthy women 9 and other independent double-blind, randomized, placebo-controlled clinical trials conducted: first on clinically healthy subjects, 11 a second on normotensive and hypertensive subjects, 12 a third on pregnant women at high risk for preeclampsia, 13 and a fourth in untreated patients with mild hypertension. 14 15 Many studies show the extent of the nocturnal BP decline is deterministic of cardiovascular injury and risk. Absence of the normal 10% to 20% sleep-time BP decline (dipper pattern) is associated with elevated risk of end-organ injury, particularly to the heart (left ventricular hypertrophy and myocardial infarct), brain (stoke), and kidney (albuminuria and progression to end-stage renal failure).…”
mentioning
confidence: 99%
“…So far, no interaction has been found, though the number of patients involved in these studies was very small (less than 19 patients). 22,23 On the other hand, Hermida et al reported an inverse association between aspirin intake (100 mg/day) given before bed-time and mean 24 hour BP levels (-6/-4 mm Hg reduction of systolic BP/ diastolic BP) 10 especially in non-dippers. 11 24 Two meta-analyses assessing the association of aspirin and other NSAIDs with BP levels have been published.…”
Section: Discussionmentioning
confidence: 99%
“…4 Results from different prospective studies conducted in the United States assessing the association between use of aspirin, NSAIDs and other analgesics and the risk of hypertension suggest that chronic users of aspirin, NSAIDS, and acetaminophen have a higher risk of hypertension. [5][6][7][8][9] However, some clinical trials conducted in Spain have shown the opposite effect 10,11 and no previous prospective study has assessed this potential relationship in a European cohort, where a different health system probably means different access to medication and a different pattern of drug use. 12 Our objective was to assess the association between regular use of aspirin and non-aspirin analgesic drugs and the incidence of HTN in a prospective dynamic cohort study consisting of Spanish university graduates, the SUN (Seguimiento Universidad de Navarra, University of Navarra Follow-up) project.…”
Section: Assessment Of Incident Hypertensionmentioning
confidence: 99%
“…161 Clinical applications of chronotherapy promise to improve treatment of a wide range of health concerns in addition to hypertension, as has been well reviewed. [163][164][165][166][167][168][169][170][171] Disregard for diurnal rhythms may contribute to differences in therapeutic efficacy, which may be observed, between nocturnal animal models and human patients. Clinical trials should routinely take into account the differing safety and efficacy profiles over 24-hour daily cycles.…”
Section: Bench To Bedside Applicationsmentioning
confidence: 99%